The Effect Of Polymer Concentration And Hydration Period On Horizontal Oil-Water Flows - Abdullah, M. Z (2008)
In this paper, the effects of polymer solution concentration and hydration period on drag reduction during oil-water flows were investigated in a horizontal 14 mm ID acrylic pipe. Exxsol D140 was used as the test oil (5.5 mPas, 828 kg/m3) while a polymer solution of partially hydrolyzed polyacrylamide (Magnafloc 1011) was added into the water stream. Low flow rates were used that resulted in stratified flow in all cases. The polymer solution concentrations in the pipeline were varied between 0 to 60 ppm, originating from two different master solutions of 500 ppm and 700 ppm. It was found that drag reduction increases as the polymer concentration in the master solution increases. Maximum drag reductions of 27% and 30% were achieved for the 500 ppm and 700 ppm master solutions, respectively. Leaving the master solution to hydrate for different periods of time (1 day, 1 week and 4 weeks), revealed that the shortest hydration time resulted in the highest drag reduction. In addition, with increasing polymer concentration in the test pipe drag reduction increased and then decreased demonstrating a maximum; this maximum was shifted to lower polymer concentration values when the master solution was hydrated for longer time